Users’ perceptions of the arrangement of links in government websites: an investigation using think-aloud and interview methods - Souto, Virgínia Tiradentes (InfoDesign, 2013)
The aim of this study is to find out what users think about the arrangement of links in government websites. The paper describes a study which used both think-aloud and interview methods. The study investigates real online government websites in the users’ natural environment of Internet use. Four online government websites are the object of the present study. It also investigates where users look first when using a government website, the search strategy and the link characteristics which help or hinder users in finding information on screen. The findings show that where the participants look first and their search strategy are both dependent on the layout of the website. In addition, the findings show the link features that help the users find information, such as a clean website, with not too many links. The findings also indicate that think-aloud and interview method is an efficient way to record users’ perceptions of real websites.